Attraction thresholds and sex discrimination of urinary odorants in male and female aromatase knockout (ArKO) mice - Pierman, Sylvie; Douhard, Quentin; Balthazart, Jacques; Baum, Michael J.; Bakker, Julie (Hormones and behavior, 2006)
We previously found that both male and female aromatase knockout (ArKO) mice, which cannot synthesize estrogens due to a targeted mutation of the aromatase gene, showed less investigation of volatile body odors from anesthetized conspecifics of both sexes in Y-maze tests. We now ask whether ArKO mice are in fact capable of discriminating between and/or responding to volatile odors. Using habituation/dishabituation tests, we found that gonadectomized ArKO and wild-type (WT) mice of both sexes, which were tested without any sex hormone replacement, reliably distinguished between undiluted volatile urinary odors of either adult males or estrous females versus deionized water as well as between these two urinary odors themselves. However, ArKO mice of both sexes were less motivated than WT controls to investigate same-sex odors when they were presented last in the sequence of stimuli. In a second experiment, we compared the ability of ArKO and WT mice to respond to decreasing concentrations of either male or female urinary odors. We found a clear-cut sex difference in urinary odor attraction thresholds among WT mice: WT males failed to respond to urine dilutions higher than 1:20 by volume, whereas WT females continued to respond to urine dilutions up to 1:80. Male ArKO mice resembled WT females in their ability to respond to lower concentrations of urinary odors, raising the possibility that the observed sex difference among WT mice in urine attraction thresholds results from the perinatal actions of estrogen in the male nervous system. Female ArKO mice failed to show significant dishabituation responses to two (1:20 and 1:80) dilutions of female urine, perhaps, again, because of a reduced motivation to investigate less salient, same-sex urinary odors. Previously observed deficits in the preference of ArKO male and female mice to approach volatile body odors from conspecifics of either sex cannot be attributed to an inability of ArKO subjects to discriminate these odors according to sex but instead may reflect a deficient motivation to approach same-sex odors, especially when their concentration is low.